A Snort-based secure edge router for smart home. (20th January 2023) - Patel, N.D.; Mehtre, B.M.; Wankar, Rajeev
Cybercrimes are rising rapidly with the increasing use of the internet of things (IoT)-based gadgets at home. For instance, the Mirai-BotNet infected and compromised many IoT-based devices and routers, creating a zombie network of robots that can be controlled remotely. There is a need for a cost-effective, secure router for a smart home. This paper investigates and proposes a Snort-based secure edge router for smart home (SERfSH), which is resilient to many cyberattacks. SERfSH automatically generates Snort content rules by combining the extracted string, location information, header information, and sequential pattern. The experimental setup of SERfSH consists of a Raspberry Pi 4 model, an ESP32 microcontroller, six IoT devices, and a malicious actor machine. The proposed SERfSH is tested for 15 attacks, and the results show that 14 attacks were detected and 12 attacks were mitigated.